Modelling the effect of chlorination/chloramination on induction of viable but non-culturable (VBNC) Escherichia coli - Chen, Sheng (Environmental technology, 2020)
Many bacteria, including Escherichia coli, are known to enter into a viable but non-culturable (VBNC) state when exposed to harsh environmental stresses. The VBNC cells introduced by chlorination/chloramination have raised increasing concern about biological safety of drinking water. A quantitative relationship between chlorination/chloramination and number of VBNC cells has not been found. In this study, a mathematical model was developed to quantify the effect of chlorination/chloramination on induction of viable but non-culturable (VBNC) Escherichia coli. the model was generated based on a first order kinetics of chlorination/chloramination using the data collected from laboratory disinfection experiments. The disinfection rates of culturable cells (kc ) and viable cells (kv ) were dose-dependent, and they were also modelled in different initial concentrations by regression analysis to overcome the shortcoming of dose-dependent. In general, the kc and kv values for chlorination (kc , 2.59-29.89 h-1; kv , 19.52-26.74 h-1) was 2-58 times greater than that for chloramination (kc , 0.5446-10.81 h-1; kv , 0.3398-14.57 h-1), suggesting that chlorine was more effective than chloramine in reducing the number of culturable and VBNC cells at same dose of disinfectant. Ultimately, the generated models, which could describe the dynamics of VBNC cells formation in chlorination/chloramination, can provide practical guidance in drinking water treatment and it can also be applied to risk assessment of drinking water management systems